1963
DOI: 10.1073/pnas.49.1.94
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Dna-Acridine Complex

Abstract: Priming by homopolynucleotides directed the incorporation of the complementary nucleotides. There was competition between the various primers suggesting that a single enzyme is involved in the reactions studied. Poly fluorouridylate was an effective inhibitor of both the DNAand polyribonucleotide-primed reactions but actinomycin D, which inhibits the reaction primed by DNA, had no appreciable effect on the polyribonucleotide-primed reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
174
1
2

Year Published

1966
1966
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(185 citation statements)
references
References 9 publications
6
174
1
2
Order By: Relevance
“…The differential staining of double-stranded DNA versus single-stranded nucleic acids (DNA or RNA) is due to the metachromatic properties of AO: the dye fluoresces green (F530) when intercalated into doublestranded nucleic acids (31) and exhibits red (F600) fluorescence when bound to single-stranded polymers (3, 25,26). A 0 stained normal, mature sperm fluoresce primarily green but at about one-tenth the level of so-matic cells due to their haploid DNA content and a high level of chromatin condensation that restricts the dye binding to DNA (9,171.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The differential staining of double-stranded DNA versus single-stranded nucleic acids (DNA or RNA) is due to the metachromatic properties of AO: the dye fluoresces green (F530) when intercalated into doublestranded nucleic acids (31) and exhibits red (F600) fluorescence when bound to single-stranded polymers (3, 25,26). A 0 stained normal, mature sperm fluoresce primarily green but at about one-tenth the level of so-matic cells due to their haploid DNA content and a high level of chromatin condensation that restricts the dye binding to DNA (9,171.…”
Section: Sample Preparationmentioning
confidence: 99%
“…It has been proposed that aminoacridines intercalate between normally neighboring DNA base pairs in a plane perpendicular to the helix axis (27); therefore, 9-AMA may be assumed to bind indiscriminately to DNA against the base pairs. This characteristic of 9-AMA should be regarded as an advantage over bromodeoxyuridine, which is often used to suppress chromosome condensation because it is strictly AT-specific and, hence, its influence on the chromosome banding pattern differs from than in AT/GC-enriched regions.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have shown that acridines are intercalated between specific adjacent base pairs in DNA (Lerman, 1963) and inhibit synthesis of DNA (Hurwitz, Furth, Malamy &Alexander, 1962). The base specificity of the affinity has been demonstrated to differ according to the kinds of acridines (Tubbs, Eitmars & van Winkle, 1964;Weisblum & de Haseth, 1972).…”
Section: Eflect Of Fatty Acids On Curingmentioning
confidence: 99%